Interdisciplinary Didactic sequence for Literacy from the "globalization" theme: Reflections for the formation of teachers (Research, Society and Development, 2019)
The knowledge areas, ‘Languages, codes and their technologies’ and ‘Human sciences and their technologies’, in High School, predict the approach of the 'globalization' theme as an essential element of the school curriculum. Although the subject is widely spoken and commented on in daily life, it has a wide scope and high complexity and can be worked with students in a critical way, especially in these two areas of knowledge. Thus, the present article intends to report the proposal of an interdisciplinary Teaching Sequence (SD) for the literacy and teaching of the globalization theme, as well as to stimulate reflections for the teacher training and qualification process. The proposal is based on multiple languages, namely: video, text and image research that translate concepts of globalization. From the Didactic Sequence - SD proposed here, it is highlighted that the use of technological and visual resources helps the student in understanding the world and in the construction of meanings through verbal and nonverbal language. In this sense, it can be inferred that pedagogical interventions, such as the one constructed by this SD, collaborate to enrich the pedagogical doing, something that needs to be practiced since the teacher training.